Integrated Waqf Environment Model (IWEM): Proposal for funding sustainable agriculture through waqf to embrace the Era of Smart Agriculture 5.0 ‎ - Maulida, Syahdatul; Rusydiana, Aam Slamet (Journal of Islamic Economics Lariba, 2025)
IntroductionAlthough global food production has tripled, sustainable agriculture remains threatened by climate change, land degradation, and financial gaps, especially in smallholder communities. This study introduces the Integrated Waqf Environment Model (IWEM) as a waqf-based funding mechanism to support sustainable agriculture. Additionally, sentiment analysis using VADER Python is employed to assess public perceptions of sustainable agriculture.ObjectivesThis research aims to measure public sentiment regarding sustainable agriculture on the Twitter social media platform. Additionally, the study proposes the Integrated Waqf Environment Model (IWEM) for sustainable agriculture funding as a response to the challenges faced in the agricultural sector.MethodThe research methodology involves the extraction and classification of tweet data using the Python library called VADER (Valence Aware Dictionary and Sentiment Reasoner). The study utilizes tweet data posted within the last year. The research findings indicate fluctuations and a decrease in the number of tweets discussing sustainable agriculture. The location with the highest tweet activity related to sustainable agriculture is Brussels, Belgium, with 642 tweets during the observation period.ResultsWord cloud analysis on keywords reveals that, in positive sentiment, terms like "food security" and "climate change" dominate the visualization. On the other hand, in negative sentiment, words like "farmer" and "private farmland" appear more frequently. Overall, the majority of tweets express a positive attitude toward sustainable agriculture, with 68.5% positive sentiment. Approximately 22.3% of tweets indicate neutral sentiment, without a strong positive or negative tendency. Only 9.1% of tweets contain negative sentiment, suggesting that a small portion expresses less supportive views of sustainable agriculture.ImplicationsThe research provides insights into public sentiment on sustainable agriculture and proposes IWEM as a sustainable financing solution. IWEM can bridge financial gaps, enhance technological adoption, and support policy development for sustainable agriculture. This model aligns with the SDGs, ensuring long-term agricultural resilience and environmental conservation.Originality/NoveltyThis study uniquely integrates Islamic social finance with Smart Agriculture 5.0 through IWEM. It also employs sentiment analysis to understand public perceptions, offering data-driven insights for policymakers. The research contributes a novel waqf-based framework that can be scaled for sustainable agricultural development.